An Artifact in Intracellular Cytokine Staining for Studying T Cell Responses and Its Alleviation - Gong, Zheng; Li, Qing; Shi, Jiayuan; Ren, Guangwen (Frontiers in Immunology, 2022)
Intracellular cytokine staining (ICS) is a widely employed ex vivo method for quantitative determination of the activation status of immune cells, most often applied to T cells. ICS test samples are commonly prepared from animal or human tissues as unpurified cell mixtures, and cell-specific cytokine signals are subsequently discriminated by gating strategies using flow cytometry. Here, we show that when ICS samples contain neutrophils, neutrophils are ex vivo-activated by an ICS reagent -- phorbol myristate acetate (PMA) -- which leads to ROS release and death of cytokine-expressing T cells. This artifact is likely to result in overinterpretation of the degree of T cell suppression, misleading immunological research related to cancer, infection, and inflammation. We accordingly devised easily implementable improvements to the ICS method and propose alternative methods for assessing or confirming cellular cytokine expression.